2020
DOI: 10.3390/pathogens9060420
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Pattern of Escherichia coli Isolated from Frozen Chicken Meat in Bangladesh

Abstract: Escherichia coli is known as one of the most important foodborne pathogens in humans, and contaminated chicken meat is an important source of foodborne infection with this bacterium. The occurrence of extended-spectrum β-lactamase (ESBL)-producing E. coli (ESBL-Ec), in particular, in chicken meat is considered a global health problem. This study aimed to determine the magnitude of E. coli, with special emphasis on ESBL-Ec, along with their phenotypic antimicrobial resistance pattern in frozen chicken meat. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 49 publications
3
39
3
1
Order By: Relevance
“…The EFSA [42] reported that ampicillin, sulfamethoxazole, tetracycline and trimethoprim were the antimicrobials most often represented in the pattern of multidrug resistance E. coli isolates from bovines, porcine and poultry species. Other studies have also reported higher resistances to tetracycline [10,13,14] and ampicillin [12,14]. For example, Zhao et al [10] reported resistance to tetracycline (50.3%) and gentamicin (18.6%) in E. coli isolated from different retail meats in the USA.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The EFSA [42] reported that ampicillin, sulfamethoxazole, tetracycline and trimethoprim were the antimicrobials most often represented in the pattern of multidrug resistance E. coli isolates from bovines, porcine and poultry species. Other studies have also reported higher resistances to tetracycline [10,13,14] and ampicillin [12,14]. For example, Zhao et al [10] reported resistance to tetracycline (50.3%) and gentamicin (18.6%) in E. coli isolated from different retail meats in the USA.…”
Section: Discussionmentioning
confidence: 97%
“…In Egypt, E. coli was detected in raw beef (54%), chicken (16%) and hand swabs from sellers (24%) [16]. According to Parvin et al [14], 76% of frozen chicken meats collected from Bangladesh were positive for E. coli. The results of Gwida et al [16] in Egypt and that of Parvin et al [14] in Bangladesh were quite similar to the findings of the current work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unethical use of antibiotics reserved for humans in veterinary practices will pose public health to a potential risk. The emergence of ESBL-producing genes and colistin-resistant mcr-1 gene in ARB is alarming considering their potentiality to reduce the efficacy of last-resort antibiotics [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%